KRITIK AL-QUR'`AN TERHADAP SAKRALISASI SIMBOL TAUHID YANG BERLEBIHAN - Satiri, Iwan; Safei, Abdullah (el-Umdah, 2022)
Research on the criticism of the Qur'an against the excessive sacralization of the monotheistic symbol is motivated by the emergence of a religious purification movement with the sacred symbols of monotheism that seeks to abolish syncretic Islamic culture. This movement claims to be the purest form of Islamic teachings, while customs are considered to be able to eliminate the authenticity of Islamic teachings so that they turn into shirk and heresy. Then this movement often disbelieves in other Muslim groups (takfirism). However, the excessive sacralization of the monotheistic symbol can actually turn the sacred symbol of monotheism into profane, if it is associated with the sacred and profane theory of Emile Durkheim which states that something sacred should not be mixed with the profane, such as the sentence of monotheism which was originally sacred (holy) turned into profane when used only for worldly purposes.